Ảnh hưởng của hệ thống thông tin đến lợi thế cạnh tranh của các công ty giao nhận hàng xuất nhập khẩu và đại lý hải quan tại TP. Hồ Chí Minh - Nguyễn Thanh , Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The objective of this study is to examine the relationship between information system capability, information system application, and competitive advantage of freight forwarding companies and customs agents in Ho Chi Minh City. This research stems from sluggish customs procedures, paper bureaucracy, and lengthy document processing at import-export forwarding and customs declaring agents. This situation is attributed to the lack of information system capacity and little usage of information systems. Data is collected from a sample of 501 forwarders and customs agents in Ho Chi Minh City. The quantitative research results show that there is a close correlation between the information system capacity and the application of information systems with the competitive advantage of these companies. The study proposes that forwarders and customs agents in Ho Chi Minh City need to apply faster and deeper information systems to increase the quality of logistics services, improve operations, especially in the fields of document processing, logistics, and operation.
Keywords: Information system; Competitive advantage; Forwarding company; Customs agent